EVALUASI KINERJA APLIKASI CCTV DINAS PERHUBUNGAN PALEMBANG DENGAN PENGUJIAN BEBAN (LOAD TESTING) - Agustian, Regi; Sauda, Siti; Jemakmun, Jemakmun; Rasmila, Rasmila (Rang Teknik Journal, 2025)
The aim of this research is to carry out load testing using the load testing method with the Apache Jmeter tool on the ACTS application for the Palembang transportation service and how optimal the load time is for the main function of the ACTS application. The data collection technique used is qualitative which contains how well the ACTS application performs. The data analysis technique used is descriptive analysis. The loading time obtained from the test results is then compared with the test target to find out how optimal the loading time of the ACTS application is. From the testing, the results obtained were that the average loading time of the ACTS application when the service was used, which was represented by the first scenario, namely 1.3 seconds and the second, namely 2.1 seconds, had met the test target, namely under 3 seconds. As for the results based on the third scenario which represents service conditions used with twice the user load, an average loading time of 4.2 seconds was obtained, which does not meet the test target. So it can be concluded that the ACTS application has worked optimally when the service is used but improvements still need to be made if the service is used by more than 650 users simultaneously.Keywords: Load Testing, Website, Apache Jmeter, Load Time, Website Application